2013
DOI: 10.1002/grl.50735
|View full text |Cite
|
Sign up to set email alerts
|

Offshore permafrost decay and massive seabed methane escape in water depths >20 m at the South Kara Sea shelf

Abstract: [1] Since the Last Glacial Maximum (~19 ka), coastal inundation from sea-level rise has been thawing thick subsea permafrost across the Arctic. Although subsea permafrost has been mapped on several Arctic continental shelves, permafrost distribution in the South Kara Sea and the extent to which it is acting as an impermeable seal to seabed methane escape remains poorly understood. Here we use >1300 km of high-resolution seismic data to map hydroacoustic anomalies, interpreted to record seabed gas release, on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 20 publications
1
86
0
5
Order By: Relevance
“…Red‐dashed lines in Figures a and b show the alternative location of the permafrost boundaries, if the sea reached its modern level at ~5 ka and remained stable until the present time. (b) Conceptual model of the West Yamal shelf, showing modern extent of continuous relict subsea permafrost based on the modeling results and the evidence of free gas expulsion recorded previously in the water column [ Portnov et al ., ]. We suppose that discontinuous patches of permafrost may still exist in the water depths >20 m. Note the different subsea and subseabed vertical scales.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red‐dashed lines in Figures a and b show the alternative location of the permafrost boundaries, if the sea reached its modern level at ~5 ka and remained stable until the present time. (b) Conceptual model of the West Yamal shelf, showing modern extent of continuous relict subsea permafrost based on the modeling results and the evidence of free gas expulsion recorded previously in the water column [ Portnov et al ., ]. We suppose that discontinuous patches of permafrost may still exist in the water depths >20 m. Note the different subsea and subseabed vertical scales.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…At the West Yamal shelf, Portnov et al . [] documented extensive seafloor gas release from the seabed into the water column, in water depths ≥20 mbsl. The authors suggested that continuous subsea permafrost, extending offshore to 20 m isobaths, provided a seal through which gas cannot migrate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biogenic and thermogenic processes associated with shallow seafloor fluid flow affect benthic ecology (Judd, 2003;Judd and Hovland, 2007). To date, the best-studied shallow seafloor release of methane was documented in the Laptev, East Siberian, and South Kara Seas, where large quantities of this powerful greenhouse gas are reaching the Arctic atmosphere (Shakhova et al, 2010;Portnov et al, 2013). Whether this flux results from warming of seafloor permafrost in these regions or has been a constant flow since the end of the last ice age requires additional long-term observations (Isaksen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reductions in its emissions would quickly diminish the rate of global warming [Forster et al, 2007]. At the same time, however, natural methane sources have the potential to significantly amplify human-induced climate change, for instance due to the strong dependence of methane wetland emissions on climate, release from permafrost soils and continental shelves, and potential destabilization of methane hydrates from the ocean floors [Kort et al, 2012;Walter-Anthony et al, 2012;Portnov et al, 2013]. While total global methane emissions from anthropogenic and natural processes at the Earth's surface are reasonably well determined [Bergamaschi et al, 2013], estimates of emissions by source sector vary by up to a factor of 2, and current ground-based observational networks fail to constrain methane emissions at regional scales [Dlugokencky et al, 2011].…”
Section: Introductionmentioning
confidence: 99%